Focus Group Discussion (FGD): The Impact Analysis of Traditional Pond Practices in Bulungan Estuary on the Community of Kampung Tias, Tanjung Palas Tengah Sub-district, Bulungan Regency - Gusman, Ery; Zainuddin, Zainuddin (Universitas Borneo Tarakan, 2024)
This FGD (Focus Group Discussion) was intended to study the impact of shrimp farming activities on biodiversity and social conditions of the community surrounding the shrimp farms, in Tias Village, Bulungan Regency. The community engagement activities are targeted to help mitigate the degradation of biodiversity and social conditions of the community as a result of shrimp farming activities. Informations were collected by organizing an inclusive meeting attended by the community, stakeholders and farmers. Discussions were semi-structured with the participants allowed to explain their perceptions of the condition of traditional shrimp farming in Muara Bulungan. The results of data collection through FGDs and interviews have given a better understanding of the impacts of traditional shrimp farming in Tias Village on both social and environmental conditions. Aquaculture activities provide economic benefits to the community, but also cause significant environmental challenges, particularly in terms of sedimentation and water quality. Integrated management efforts with active participation from the community, industry and government are required to ensure the sustainability of fisheries resources and maintain ecosystem integrity. Recommendations include replanting mangroves and developing a hatchery for mangrove crabs to conserve coastal biodiversity, which can contribute to sustaining the ecosystem and improving community livelihoods.